(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The interpretation of distance education notion by Ukrainian and foreign scientists is considered in the article. The main stages of the development (analysis, planning and design) of the distance course "Databases and Information Systems" taking into account scientific basis of selection of educational material content are highlighted.